Comparing the effects of first‐line antiepileptic drugs on the gait of dogs with idiopathic epilepsy. (25th June 2016) - Suiter, E. J.; Packer, R. M. A.; Volk, H. A.
Abstract : Idiopathic epilepsy (IE) is a common chronic neurological disease of the dog. Previous studies of anti‐epileptic drug (AED) treatment have indicated that acceptable AED adverse effects are as important to owners as reductions in seizure frequency. AEDs in both dogs and human beings are frequently associated with the adverse‐effect ataxia. The aim of this study was to compare ataxia levels in dogs with IE treated chronically with phenobarbitone or imepitoin, the two currently available first‐line AED treatments. The gait of 6 imepitoin‐treated dogs, 8 phenobarbitone‐treated dogs and 10 age‐matched healthy control dogs were compared. Fifty strides from a walking gait were analysed for each dog, quantifying ataxia via the variability in six established gait parameters. Three variables differed significantly between groups: lateral distance between (i) pelvic paw placements, (ii) thoracic paw placements and (iii) stance time, which were significantly more variable in the phenobarbitone‐treated dogs than imepitoin‐treated or control dogs. These results indicate that dogs treated with phenobarbitone experience ataxia compared with controls and imepitoin‐treated dogs. Conversely, there was no difference between imepitoin‐treated dogs and controls. These results along with further research are needed to quantify AEDs adverse effects, to help vets and owners make more informed drug‐choices.